Service Quality and Customer Satisfaction in Uganda Registration Services Bureau (URSB) - Lukia Nantume (Uganda Christian University, 2026)
This study examines the relationship between service quality and customer satisfaction at the Uganda Registration Services Bureau (URSB). The research is grounded in the SERVQUAL model and Expectancy-Disconfirmation Theory, focusing on five key dimensions of service quality: reliability, responsiveness, assurance, empathy, and tangibility. A cross-sectional research design was adopted, combining both quantitative and qualitative approaches. Data were collected from 27 URSB clients through structured questionnaires and supplemented with interviews from selected staff. The findings reveal that overall service quality at URSB is perceived as satisfactory, with assurance emerging as the most significant determinant of customer satisfaction, followed by reliability and tangibility. Responsiveness and empathy, although positively related, were found to have a weaker and statistically insignificant influence on customer satisfaction. Regression analysis indicates that service quality explains approximately 50.7% of the variation in customer satisfaction. Despite ongoing reforms such as digitalization and decentralization, challenges including service delays, system downtimes, and limited personalized attention persist. The study concludes that improving service quality—particularly staff professionalism, system reliability, and communication efficiency—can significantly enhance customer satisfaction, trust, and service utilization. The research provides practical recommendations for URSB management and policymakers to strengthen service delivery and public sector performance.
Undergraduate